A SPEECH ACT ANALYSIS: ILLOCUTIONARY ACTS PRODUCED BY TEACHER IN ESL CLASSROOM - Alif Aribah Yulian; Vidya Mandarani (University of Muhammadiyah Malang, 2023)
Speech acts determine classroom interaction. Speech acts consist of all verbal utterances used in classroom communication. This study identified and described the forms of speech acts based on Searle’s illocutionary act theory produced by the teacher to the seventh grader of the International class program at SMP Muhammadiyah 1 Sidoarjo. The primary focus was on the utterances of the English as a second language teacher. In this study, researchers employed a descriptive qualitative method. Observations and recordings were used to acquire the data. The obtained data were then transcribed and analyzed using NVivo 12 Pro. The teacher produces two hundred and sixty-six utterances and four kinds of Searle’s illocutionary acts in the English as a second language classroom. Sixty-eight of their statements were representative, one hundred fifty-one were directive, five were commissive, and forty-two were expressive. The teacher’s frequent use of instructions suggests that she was conscious of her position as a more powerful individual than her students and efficiently managed and commanded the classroom.